(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Plants may be protected against pests with the use of pesticides, however during the last fortyyears, widespread pesticide usage has disrupted the natural biological system. Some agriculturalherbicides have the potential to damage microorganisms that fix nitrogen. Studying how pesticides affectmicroorganisms that fix nitrogen was the goal of the current investigation. Actually, the purpose of theresearch was to determine how the herbicides affected the desirable nitrogen-fixing bacteria, which arecrucial for plant development and higher yields. In comparison to the growth of herbicide significantlyreduced both nitrogen-fixing bacteria. This study’s findings support the notion that pesticides operatedifferently at various areas and have varying effects on the development of bacteria that fix nitrogen.Evidence suggests that the pesticides used in field conditions may have had a negative impact on thepopulation of these bacteria because of their high toxic nature.